Quality of Walkability in Peunayong, Banda Aceh - Adil Mushaithir Darmawan; Dwita Hadi Rahmi (Built Environment Studies, 2021)
Walking is an important element of accessibility because it can increase the livability of a city. Peunayong as a trade and service center as well as a heritage area has very diverse activities with high intensity. The density of activities in Peunayong causes high vehicle accessibility which causes congestion in the area, parking on site which narrows the space for pedestrians and vehicles. In addition, pedestrian facilities in Peunayong still do not facilitate pedestrians because of the mixing of various activities in one lane, such as circulation, parking, and trading. In creating a pedestrian-friendly, it is necessary to plan and design good pedestrian facilities, by paying attention to the characteristics of pedestrians and their district. Walkability is one of the concepts for a walkable area. The approach in this study is by adopting the walkability theory as a reference. The focus of this research is to determine the quality of walkability in Peunayong. The method of analysis uses descriptive analysis. Those that formed walkability which will become parameters in this study are Connected, Convenient, Comfort, Convivial, Conspicuous through pedestrian paths and crossings, circulation activity, block size, spatial enclosure and humanscale, open space and vegetation, street furniture and signage.